(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Motivation: Nearly 2000 mitral valve repair surgeries are performed within the UK every year, providing patients with a less invasive surgery and improved outcomes compared to full valve replacement. Whilst a number of developments have been made in technologies such as minimally invasive valve repairs, newer devices used to complete the surgery have not been widely developed or adopted. In this work we investigated the use of additive manufacturing to provide patient-centred and personalised devices for repair surgery. Materials and Methods: Investigations into the dimensions of existing marketed annuloplasty devices compared to those of human mitral valves were undertaken in cadaver studies. A design method for production of devices was developed using commercially available software and 3D ultrasound scans. Investigations into the material safety of additively manufactured materials were undertaken to ensure hemocompatibility of the devices and prevention of thrombogenesis associated with the foreign object. Improvement of surface integration into the body was attempted using novel polishing techniques and surface modification with biological agents. Results and Discussion: Existing marketed annuloplasty devices were shown to be insufficient across a population to provide accurate, healthy anatomy, given individual variation in shape. Design based on ultrasound scans was shown to be possible through an alternative method not relying on density variations as used in thresholding of bone for bespoke design. Additively manufactured titanium alloys were shown to be significantly thrombogenic, but novel polishing techniques were effective in controlling this risk, however this reduced the efficacy of cell integration into the device. Conclusion: This research has shown the potential for application of bespoke additively manufactured implants in mitral valve repair. The design, safety, and integration of the device have been investigated and pathways for future development in computational analysis and material properties have been discussed.